2016
DOI: 10.1371/journal.pone.0155797
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of NIPAM Polymer Gel Dosimeters on Three Orthogonal Planes and Temporal Stability Analysis

Abstract: Polymer gel dosimeters have been proven useful for dose evaluation in radiotherapy treatments. Previous studies have demonstrated that using a polymer gel dosimeter requires a 24 h reaction time to stabilize and further evaluate the measured dose distribution in two-dimensional dosimetry. In this study, the short-term stability within 24 h and feasibility of N-isopropylacrylamide (NIPAM) polymer gel dosimeters for use in three-dimensional dosimetry were evaluated using magnetic resonance imaging (MRI). NIPAM g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is important to note that this process is extremely fast when the solution is cooled down below 35 °C, but the evolution is much slower in later phases. This process can take up to 30 daysor longer and may cause shrinkage of the gel by losing water, which leads to the density changes in irradiated gels contributing to the evolution/instability in the dose responses [ 10 , 39 , 43 , 44 , 45 ]. Post-irradiation polymerization reactions progress up to 10 h after the irradiation [ 19 , 42 ], however, they do not fully stop due to the presence of remaining long-term radicals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that this process is extremely fast when the solution is cooled down below 35 °C, but the evolution is much slower in later phases. This process can take up to 30 daysor longer and may cause shrinkage of the gel by losing water, which leads to the density changes in irradiated gels contributing to the evolution/instability in the dose responses [ 10 , 39 , 43 , 44 , 45 ]. Post-irradiation polymerization reactions progress up to 10 h after the irradiation [ 19 , 42 ], however, they do not fully stop due to the presence of remaining long-term radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The successful application of imaging modalities (MRI and OCT) for the evaluation of polymer gel dosimeters applicability in the small field dosimetry are provided in studies [ 38 , 39 ], where it was shown that the normoxic NIPAM polymer gel dosimeters can be applied for the assessment of small field dose deliveries using both read out techniques: cone beam optical computed tomography and MRI. Both methods indicated an acceptable gamma passing rate (<1) since a voxel agreement of 95% for the target level was achieved between the treatment plan and gel-measured dose distributions, applying 3% dose and 3 mm distance-to-agreement gamma function criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration tubes filled with NIPAM gel exposed to given doses (reported in Figure A ) are located around the centran phantom. Reproduced from [ 64 ].…”
Section: Figurementioning
confidence: 99%